Gatunki pierwotne i wtórne w perspektywie historycznej i współczesnej - Wilkoń, Aleksander (Er(r)go. Teoria - Literatura - Kultura, 2001)
Aleksander Wilkoń Primary and Secondary Genres in Two Perspectives: an Historical One and a Contemporary One Aleksander Wilkon's essay challenges some of Mikhail Bakhtin's conceptions which have been taken for granted in textual linguistics and genology. Wilkon is particularly critical of those generalisations which ignore the categories of the individual, the non-systemic and the inimitable Regardless of their inspirations, the generalisations have tended to lead to simplifications and schematism. In the second section of his essay Wilkon questions Bakhtin's division into primary and secondary genres, which comes down to a distinction between utilitarian genres (both spoken and written) and their literary transformations and mutations. Wilkon argues that Bakhtin's overlooks the influence of secondary genres on those genres which function as primary ones and at the same time derive from literary forms. In the final section of the essay its author identifies secondary genres within spoken forms of language, which include magic speech, the speech of play and customs and folk art speech.